2021
DOI: 10.17309/tmfv.2021.4.01
|View full text |Cite
|
Sign up to set email alerts
|

A Discriminant Model For Skill Oriented Prediction of Female Cricketers Depending Upon Selected Performance Parameters

Abstract: Research Purpose. The study aimed to develop a discriminant model for cricketers on the basis of physiological & anthropometric variables. Material and Methods. The study included sixty female seniors BCCI board players representing five different states with mean age 23.4 ± 2.03, mean height 152.1 ± 3.44, and mean weight 52.4 ± 4.21. A multivariate technique was used to predict the cricket performance by classifying the players into batsmen and pace bowlers on the basis of selected physiological &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The Inverse MultiQuadratic kernel proves to be a standout choice for predicting the most valuable player in the WPL 2024 season. Its efficacy in capturing the dynamics of women's premier league cricket positions it as a valuable tool for stakeholders, aiding in strategic decision-making and enhancing overall understanding of player performances in this evolving sporting landscape (Mandoli et al, 2021;Passi and Pandey, 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…The Inverse MultiQuadratic kernel proves to be a standout choice for predicting the most valuable player in the WPL 2024 season. Its efficacy in capturing the dynamics of women's premier league cricket positions it as a valuable tool for stakeholders, aiding in strategic decision-making and enhancing overall understanding of player performances in this evolving sporting landscape (Mandoli et al, 2021;Passi and Pandey, 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the discriminant analysis, it was found that motor fitness can be controlled based on the regression equation set out in column 5 (Table 4) and the comparison between the result obtained and the function value at group centroids (2.262). The data set out supplement the data on the use of discriminant analysis in physical education of schoolchildren (Mandoli, Sharma, & Joshi, 2021;Siedykh, Ivashchenko, Bartik, & Veremeenko, 2022;Mugurdinova, & Iermakov, 2022).…”
Section: Discussionmentioning
confidence: 99%